PENGGUNAAN MULTIMEDIA INTERAKTIF BERBASIS FLASH PRO 8 UNTUK MENINGKATKAN EFEKTIFITAS PERKULIAHAN GENETIKA - Jefri Handika; Sri Utami; Tantri Mayasari (Jurnal Pendidikan, 2012)
This research is served to develop teaching instruments which refer to 4-D Model, including: interactive multimedia, Lesson Plan, Syllabus, Student Worksheet and Evaluation, for the subject of Genetics through two-cycle action research. This research aso attempts to develop the effectiveness of teaching by the application of teaching media which visualize the abstract concepts of the Genetics class consisting of 42 students of semester IV class D of Biology Study Program, the Faculty of Natural Science and Mathematics, IKIP PGRI MADIUN. Teaching process is implemented by One Group Pretest-Posttest Design, and the data are analyzed descriptively. The analysis results in conclusions that: the teaching-learning  scenario is carried out well, learning acitivities are well-developed by the use of multimedia instruments. The observation finds that one student has higher level of learning activities than the average of others by using multimedia instruments by 34.57% at the Lesson Plan 1, 28.14% at the Lesson Plan 2, and 45.57% at the Lesson Plan 3. Interactive multimedia model of teaching is able to put students above the classical threshold level by 97.2% leaving one student under the treshold level. Good response against the ineractive multimedia model of teaching is given by 43 students or 81.02%, good response against the teaching materials is 100%. Some aspects which have to be considered are: lecturer has to be well-prepared; students have to be well-assisted in using interactive multimedia apparatus; assurance that students with their own computer apparatus have the required programs and applications; strict coordination among lecturers in utilizing the infrastructures.